Voltammetric quantification of 4-nitrophenol using a multivariate optimized plated bismuth film electrode - Núñez, Rodrigo Nicolás (2019)
In this study the multivariate optimization of bismuth film deposition (BiFE) on glassy carbon electrode, together with square wave voltammetry parameters for nitrophenol quantification, is described for the first time. For this purpose, response surface methodology and desirability function were applied to a Box-Behnken design. For the BiFE deposition procedure, the relationship between the reduction current peak (ip) and standard deviation values with time, potential deposition, and Bi(III) concentration were analyzed; meanwhile, for frequency, step, and amplitude only the relationship with ip was considered. The pH influence in nitrophenol determination was carried on by univariate analysis. After parameters optimization a limit of detection of 3.4 × 10-6 mol L-1 was observed.